Ramshackle ode - Leonard, Keith (Keith R.) (2016)
Containing joy and suffering side by side, Ramshackle Ode offers elegies and odes as necessary partners to bring out the greatest power in each. By turns celebratory, meditative, tender, and rebellious, these poems reimagine the divisions and intersections of life and death, the human and the natural world, the brutal and the beautiful. Time and again, they choose hope
"A Mariner original"
Keywords: American poetry -- 21st century